Home telehealth and paediatric palliative care: clinician perceptions of what is stopping us? - Bradford, Natalie K (BioMed Central, 2014)
BACKGROUND: Advances in technology have made the use of telehealth in the home setting a feasible option for palliative care clinicians to provide clinical care and support. However, despite being widely available and accessible, telehealth has still not been widely adopted either in Australia or internationally. The study aim was to investigate the barriers, enablers and perceived usefulness for an established home telehealth program in paediatric palliative care from the perspective of clinicians. METHODS: Semi-structured interviews (n = 10) were undertaken with palliative care clinicians in a tertiary paediatric hospital to identify attitudes to, satisfaction with, and perceived benefits and limitations of, home telehealth in palliative care. Iterative analysis was used to thematically analyse data and identify themes and core concepts from interviews. RESULTS: Four themes are reported: managing relationships; expectations of clinicians; co-ordination, and the telehealth compromise. Core concepts that emerged from the data were the perceived ability to control clinical encounters in a virtual environment and the need to trust technology. These concepts help explain the telehealth compromise and low utilisation of the home telehealth program. CONCLUSIONS: Effective communication between caregivers and clinicians is recognised as a core value of palliative care. Home telehealth has the potential to provide a solution to inequity of access to care, facilitate peer support and maintain continuity of care with families. However, significant limitations and challenges may impede its use. The virtual space creates additional challenges for communication, which clinicians and families may not intuitively understand. For home telehealth to be integrated into routine care, greater understanding of the nature of communication in the virtual space is required.